2013
DOI: 10.1002/pssr.201308092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of precursor gas ratio and firing on silicon surface passivation by APCVD aluminium oxide

Abstract: Using a high throughput, in‐line atmosphere chemical vapor deposition (APCVD) tool, we have synthesized amorphous aluminum oxide (AlOx) films from precursors of trimethyl‐aluminum (TMA) and O2, yielding a maximum deposition 150 nm min–1 per wafer. For p‐type crystalline silicon (c‐Si) wafers, excellent surface passivation was achieved with the APCVD AlOx films, with a best maximum effective surface recombination velocity (Seff,max) of 8 cm/s following a standard industrial firing step. The findings could be at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…During the APCVD oxide film deposition process, monocrystalline Si wafers (polished and textured) were placed on a continuously moving belt at the entry port and horizontally transported through the CVD deposition chambers. Trimethylaluminum and O 2 were used as precursors for the AlO x deposition [7]. For the SiO x films, silane and O 2 were used [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the APCVD oxide film deposition process, monocrystalline Si wafers (polished and textured) were placed on a continuously moving belt at the entry port and horizontally transported through the CVD deposition chambers. Trimethylaluminum and O 2 were used as precursors for the AlO x deposition [7]. For the SiO x films, silane and O 2 were used [18].…”
Section: Methodsmentioning
confidence: 99%
“…In-line processes can help minimize contact between wafers and wafer handling systems, which is especially beneficial for thin wafer formats below 150 μm [5]. APCVD TiO x films have been utilized as single-and double-layer ARCs (DLARC) in the past [6], and recent work has demonstrated that APCVD AlO x films can provide excellent passivation of p-type surfaces [7], [8]. In this paper, the optical and microstructural properties of APCVD TiO x films are presented for varied deposition temperatures (T dep ) and precursor gas ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional passivation of n-type emitter surface in silicon solar cell is mainly achieved with dielectric materials like SiN x , SiO 2 and Al 2 O 3 . In these passivation schemes, the processes require high temperatures between 100°C and 1000°C for obtaining a high quality passivating layers (Aberle, 2000;Wenham et al, 2001;Lee and Glunz, 2006;Bousbih et al, 2012;Pudasaini et al, 2013aPudasaini et al, ,b, 2014Davis et al, 2013), amounting significant energy input toward solar cell fabrication. The aforementioned demand of high temperature is also detrimental for quality of the bulk Si apart from increase in the upfront costs of solar cell (Koyama et al, 2010;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In The corona-Kelvin metrology has been used extensively to characterize PV dielectrics on planar surfaces as evidenced by numerous publications on the subject [2][3][4][5][6]. Although users of the corona-Kelvin technique may have been characterizing PV dielectrics on textured surfaces, very little if any work has been published on this topic.…”
Section: Introduction and Outline Of The Approachmentioning
confidence: 99%